Modification of the ID-Fungal (IMMY) in Immune-Diagnosis of Deep Mycosis - Magaldi Sylvia; Reyes Heidi; Hartung de Capriles Claudia; Mata-Essayag Sofía; Pérez, Celina; Colella María Teresa (Kasmera, 2003)
Abstract: This technical report describes the modifications made in ID-Fungal anti-bodies in the IMMY line in fungus serology. The first part is related to the increase in the sensitivity of the technique due to the concentrations of serum, which doubles the quantity of the same when added to diffusion wells. This procedure is useful basically in immune-compromised patients in which the quantity of blood antibodies is low. The second modification helps to facilitate the reading of precipitation bands through bright blue coloring with Coomassie, which at the same time aids the preservations and storage of the plates over time.